Atos e fatos da formação profissional - Dannemann, Robert Nicolaus (Boletim Técnico do Senac, 2004)
This article discusses concepts of vocational training and education, listing types of activities and courses through which vocational education is imparted in Brazil. The article emphasizes that increasingly effective articulation between formal education and vocational training systems corresponds to the essential principles of integrity and continuity that direct education in modern society. Its reasoning is based on legal provisions – laws, decrees, decree-laws, bylaws, legal statements, recommendations, and so on – that deal with vocational education.